Typological and experimental approaches in the study of quarry lithic technology: cases from northwestern and central eastern of Argentina - Bobillo, Federico Miguel; Colombo, Mariano (Facultad de Filosofía y Humanidades. Museo de Antropología, 2023)
The typological and experimental studies in pre-hispanic quarries allow us to know the technological strategies, social practices and the making proceses and use of knapped tools. This work analyzes how the combination and complementarity between typological and experimental studies constitutes a highly relevant procedure for understanding the variability of activities and techniques used in the raw materials procurement. For this analysis, the case of the vulcanite quarries-workshop of Antofagasta de la Sierra (northwest Argentina) and the quartzite quarries of the Sierras de Tandilia (central-east of Argentina) are considered. In both cases, lithic procurement is studied from an integrative approach. In this sense, the qualitative attributes of the materials on which a certain technique is applied, the energy implemented by the individuals, the tool kits used, the technical gestures (sustained or thrown percussion) and the knowledge required for the different techno-utilitarian and social practices carried out there are analyzed.